Pengembangan Diktat Fisika Berbasis Problem Based Learning untuk Meningkatkan Kemampuan Berpikir Kritis Peserta Didik - Khoirun Nisa; Ashari Ashari; Eko Setyadi Kurniawan (Universitas Muhammadiyah Purworejo, 2019)
Research on the development of physics-based dictates based on Problem Based Learning has been carried out to determine the feasibility of the developed physics dictates, students 'responses to the developed physics dictates, and increasing students' critical thinking. The type of research used is a development that refers to the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation). The subjects of this study were the students of class XI MIPA 2 of SMA Negeri 11 Purworejo, totaling 30 students. The material developed is Dynamic Fluid. Data collection techniques This study was conducted using interviews, observation, questionnaires, tests, and documentation. The data obtained in the form of qualitative and quantitative data, while the data analysis using the Percentage Agreement. Based on the results of the study, the average score obtained from expert lecturers was 3.47, and physics teachers were 3.27 with